Pengaruh Likuiditas, Profitabilitas, dan Ukuran Perusahaan Terhadap Nilai Perusahaan - Ammy, Baihaqi (Jurnal Riset Akuntansi dan Bisnis, 2024)
The problem of this study is the occurrence of a significant decrease and increase in the current ratio, and return on assets can affect the value of the company, the increase in company size is not accompanied by an increase in company value. The purpose of this study is to: (1) determine and analyze the effect of liquidity, profitability, and company size on company value and to determine and analyze the effect of liquidity as measured by the current ratio, profitability as measured by return on assets, and company size as measured by the natural logarithm on company value as measured by price to book value. This study uses a descriptive statistical research type. The population in the study was PT. Perkebunan Nusantara IV Medan and a sample of 5 years of observation. Based on the results of the study, it showed that liquidity had a negative but insignificant effect on company value, profitability did not have a significant effect on company value, and company size had a significant effect on company value. Based on the results, simultaneously, liquidity, profitability and company size did not have a significant effect on company value.